The Endomorphism Monoids of (n − 3)-regular Graphs of Order n - Gyurov, B.; Knauer, U.; Panma, S.; Pipattanajinda, N. (Algebra and Discrete Mathematics, 2016)
This paper is motivated by the result of W. Li, he presents an infinite family of graphs - complements of cycles - which possess a regular monoid. We show that these regular monoids are completely regular. Furthermore, we characterize the regular, orthodox and completely regular endomorphisms of the join of complements of cycles, i.e. (n−3)-regular graph of order n.